Diffusion of indigenous fire management and carbon-credit programs: Opportunities and challenges for “scaling-up” to temperate ecosystems - Nikolakis, William; Welham, Clive; Greene, Gregory (Frontiers in Forests and Global Change, 2022)
Savanna burning programs across northern Australia generate millions of dollars per year for Indigenous communities through carbon markets. In catalyzing Indigenous knowledge and workforce to mitigate destructive wildfires, these programs are considered a success story on a range of social, ecological and economic measures. Scaling-up to temperate ecosystems requires a focus on applying the architecture and governance of these programs, and accounting for fundamental differences in context. We examine the opportunities and challenges in applying the architecture of savanna burning to an Indigenous fire management (IFM) program in central British Columbia, Canada (the Chilcotin). We draw from eight key elements of the Australian savanna burning model to identify a project area that includes Aboriginal title and reserve lands. The area encompasses dry forest and grassland ecosystems where low intensity fires are applied by community members to remove forest fuels, with the goal of mitigating wildfires and associated GHG emissions. The multi-decadal intervals between contemporary fires in the Chilcotin region make it challenging to accurately document historical fire location, scale and intensity, and thus to establish an emissions baseline. If this issue can be resolved, the British Columbia Forest Carbon Offset Protocol version 2 (FCOPv2) offers promise for developing verified carbon credits for three reasons: first, carbon (CO2), nitrous oxide (N2O), and methane (CH4), the three main GHG emissions from Indigenous fire management, are included in the protocol; second, credits under FCOPv2 are eligible for either compliance or voluntary markets, offering diversification; and third, a range of activities are eligible under the standard, including fire management and timber harvesting, which offers flexibility in terms of management practices. The Chilcotin project is likely to generate substantial co-benefits related to cultural, health and wellbeing, and livelihood values among First Nations participants. The Australian experience suggests that getting governance right, and building community ownership through ‘bottom-up’ governance, is critical to the success of these programs. From the Australian model, community-based planning, like the Healthy Country Planning approach, can be a positive step to take, engaging community in goal setting for the program to guide and take ownership of its direction.